2006
DOI: 10.1029/2005gl025605
|View full text |Cite
|
Sign up to set email alerts
|

P‐wave tomography reveals a westward dipping low velocity zone beneath the Kenya Rift

Abstract: Three teleseismic P‐wave travel time data sets (KRISP 1985, 1989–1990; Kenya Broadband Seismic Experiment) have been inverted to obtain a new tomographic model of the upper mantle beneath the Kenya Rift. The model shows a 0.5–1.5% low velocity anomaly below the rift extending to about 150 km depth. Below ∼150 km depth, the anomaly broadens to the west toward the Tanzania Craton, suggesting a westward dip to the structure. Tomographic images to the south in Tanzania and to the north in Ethiopia also show westwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 27 publications
7
52
1
1
Order By: Relevance
“…[11] A P wave tomography study of the mantle beneath Kenya by Park and Nyblade [2006] also revealed the presence of a LWA dipping to the west beneath the Tanzania Craton, consistent with earlier tomographic models from the Kenya Rift International Seismic Project (KRISP) [Green et al, 1991;Achauer and the KRISP Teleseismic Working Group, 1994;Achauer and Masson, 2002]. The limited resolution imposed by the small aperture of the Tanzania and Kenya networks, however, made it difficult for these studies to show conclusively whether the westward dipping LWA continued at depth beneath the Tanzania Craton connecting to a similar LWA under the Western branch, and also if the LWA extended through the transition zone.…”
Section: Previous Seismic Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…[11] A P wave tomography study of the mantle beneath Kenya by Park and Nyblade [2006] also revealed the presence of a LWA dipping to the west beneath the Tanzania Craton, consistent with earlier tomographic models from the Kenya Rift International Seismic Project (KRISP) [Green et al, 1991;Achauer and the KRISP Teleseismic Working Group, 1994;Achauer and Masson, 2002]. The limited resolution imposed by the small aperture of the Tanzania and Kenya networks, however, made it difficult for these studies to show conclusively whether the westward dipping LWA continued at depth beneath the Tanzania Craton connecting to a similar LWA under the Western branch, and also if the LWA extended through the transition zone.…”
Section: Previous Seismic Studiesmentioning
confidence: 99%
“…[Color figure can be viewed in the online issue, which is available at wileyonlinelibrary.com.] Park and Nyblade, 2006] and Ethiopia [Bastow et al, 2005[Bastow et al, , 2008Benoit et al, 2006].…”
Section: Relative Arrival Time Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies are dedicated to investigations of relatively small segments of the EARS using different tomographic methods (e.g. Daly et al, 2008;Jakovlev et al, 2011;Park and Nyblade, 2006;Tongue, 1992). Here I present a regional tomographic model of the upper mantle beneath the EARS constructed by Koulakov (2007) and based on global catalogues using the regional tomographic scheme shown in Figure 1.…”
Section: East African Rift System: Plumes or Convective Flows?mentioning
confidence: 99%